Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025737
|View full text |Cite
|
Sign up to set email alerts
|

Understanding "Death by GPS"

Abstract: Catastrophic incidents associated with GPS devices and other personal navigation technologies are sufficiently common that these incidents have been given a colloquial nickname: "Death by GPS". While there is a significant body of work on the use of personal navigation technologies in everyday scenarios, no research has examined these technologies' roles in catastrophic incidents. In this paper, we seek to address this gap in the literature. Borrowing techniques from public health research and communication st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Despite the popularity of navigation systems, concerns have been raised in the literature about the negative effects on spatial knowledge acquisition caused by their extensive use (e.g., Gardony, Brunyé, Mahoney, & Taylor, 2013; Klippel, Hirtle, & Davies, 2010; Montello, 2005). These systems consume most of a pedestrian’s attention, leading to decreased spatial knowledge (Parush, Ahuvia, & Erev, 2007) and even to fatal accidents (Lin, Kuehl, Schöning, & Hecht, 2017) due to divided attention between the survey perspective offered by the navigation system and the route perspective, i.e., the first-person view (Gardony et al, 2013). As the trend towards using navigation systems increases, a considerable amount of literature has recently examined how navigation systems negatively affect spatial knowledge acquisition and human navigation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of navigation systems, concerns have been raised in the literature about the negative effects on spatial knowledge acquisition caused by their extensive use (e.g., Gardony, Brunyé, Mahoney, & Taylor, 2013; Klippel, Hirtle, & Davies, 2010; Montello, 2005). These systems consume most of a pedestrian’s attention, leading to decreased spatial knowledge (Parush, Ahuvia, & Erev, 2007) and even to fatal accidents (Lin, Kuehl, Schöning, & Hecht, 2017) due to divided attention between the survey perspective offered by the navigation system and the route perspective, i.e., the first-person view (Gardony et al, 2013). As the trend towards using navigation systems increases, a considerable amount of literature has recently examined how navigation systems negatively affect spatial knowledge acquisition and human navigation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Oppositely, errors of omission occur when the human operator did not take appropriate action because the decision aid failed to provide advice (Skitka et al 1999). Lin et al (2017) reviewed 158 errors of omission and commission associated with the use of GPS devices while driving, 28% of which involved a fatality.…”
Section: Pitfall 5: Misusementioning
confidence: 99%
“…However, even when the system works properly, the risk of getting lost remains based on inadequate application of or over-reliance on the navigation assistance system. This was revealed in in a corpus of 158 so called "Death by GPS" incidents published in the English news between 2010 and 2017 (Lin et al, 2017) .…”
Section: Introductionmentioning
confidence: 96%
“…One finding showed that the use of automated assistance systems was associated with divided attention between the movement related task and the assisted navigation (Fenech et al, 2010;Gardony et al, 2013;Gardony et al, 2015). This resource allocation conflict increases the reliance on the navigation assistant in order to reduce attentional demands (Baus et al, 2001;Klippel et al, 2010;Parush et al, 2007) leading to an automation bias (Lin et al, 2017). The users tend to hand over the decision-making to the automated system (Bakdash et al, 2008;Fenech et al, 2010;Parush et al, 2007).…”
Section: Introductionmentioning
confidence: 99%